The effect of inflation rate, interest rate and unemployment rate towards Gross Domestic Products (GDP) growth rate / Nurul Shakilla Hussin and Syaikhul Solihin Samsudin - Hussin, Nurul Shakilla; Samsudin, Syaikhul Solihin (Faculty of Business and Management, 2016)
Gross Domestic Products (GDP) growth rate is depending on the fiscal policy and other related factors. In this study, the researchers want to investigate the factors that contribute to Gross Domestic Products (GDP) growth rate by using time series data quarterly from 2006 to 2014 in Malaysia. The researchers want to estimate whether the independent variables have the relationship with Gross Domestic Products (GDP) growth rate in Malaysia. Findings show that only unemployment rate is significant towards Gross Domestic Products (GDP) growth rate while inflation rate and interest rate do not have significant relationship with Gross Domestic Products (GDP) growth rate. The researchers used secondary data in this study. In addition, the researchers also used Static Ordinary Least Square Method which consists of Single Linear Regression and Multiple Linear Regression to test the data collected. The researchers used both method in order to get strong result at the end of the analysis. Finally, we have come out with the conclusion and recommendation for the betterment of Malaysia in the future.